2017
DOI: 10.1371/journal.pone.0173001
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of gun violence in Syracuse, New York 2009-2015

Abstract: Gun violence in the United States of America is a large public health problem that disproportionately affects urban areas. The epidemiology of gun violence reflects various aspects of an infectious disease including spatial and temporal clustering. We examined the spatial and temporal trends of gun violence in Syracuse, New York, a city of 145,000. We used a spatial scan statistic to reveal spatio-temporal clusters of gunshots investigated and corroborated by Syracuse City Police Department for the years 2009–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 28 publications
1
23
0
3
Order By: Relevance
“…Previous studies have shown that signs of disorder are correlated with concentrated disadvantage (Gau and Pratt, 2010;Sampson and Raudenbush, 2004;Wilcox et al, 2004). Measures of neighborhood disadvantage (e.g., poverty, unemployment, family income, literacy, welfare) and neighborhood instability (e.g., residential mobility and divorciality) have been associated to spatial variations of homicide (Akins, Rumbaut, and Stansfield, 2009;Barata et al, 1998;Berezin et al, 2017;Boessen and Hipp, 2015;Ferrandino, 2018;Hannon, 2005;Kubrin and Weitzer, 2003;Larsen et al, 2017;Mancik, Parker, and Williams, 2018;Mares, 2010;Nieuwbeerta et al, 2008;Ousey, 2006;Parker and McCall, 1999;Pereira, Mota, and Andresen, 2017;Santos, Barcellos, and Sacarvalho, 2006;Strom and MacDonald, 2016;Suresh and Vito, 2009;Vilalta, Castillo, and Torres, 2016;Vilalta and Fondevila, 2019;Vilalta and Muggah, 2014).…”
Section: Homicide and Concentrated Disadvantagementioning
confidence: 99%
“…Previous studies have shown that signs of disorder are correlated with concentrated disadvantage (Gau and Pratt, 2010;Sampson and Raudenbush, 2004;Wilcox et al, 2004). Measures of neighborhood disadvantage (e.g., poverty, unemployment, family income, literacy, welfare) and neighborhood instability (e.g., residential mobility and divorciality) have been associated to spatial variations of homicide (Akins, Rumbaut, and Stansfield, 2009;Barata et al, 1998;Berezin et al, 2017;Boessen and Hipp, 2015;Ferrandino, 2018;Hannon, 2005;Kubrin and Weitzer, 2003;Larsen et al, 2017;Mancik, Parker, and Williams, 2018;Mares, 2010;Nieuwbeerta et al, 2008;Ousey, 2006;Parker and McCall, 1999;Pereira, Mota, and Andresen, 2017;Santos, Barcellos, and Sacarvalho, 2006;Strom and MacDonald, 2016;Suresh and Vito, 2009;Vilalta, Castillo, and Torres, 2016;Vilalta and Fondevila, 2019;Vilalta and Muggah, 2014).…”
Section: Homicide and Concentrated Disadvantagementioning
confidence: 99%
“…Violence continues to be a serious public health problem in different regions of the world due to reflections on health indicators, influence on the daily lives of individuals and the constant presence of victims in health services . According to data from the World Health Organization, 1.4 million people lose their lives annually and many others sustain non‐fatal injuries resulting from episodes of violence .…”
Section: Introductionmentioning
confidence: 99%
“…Ressalta-se que a violência guarda relações profundas com a estrutura social, econômica e política. Aprofunda-se com as exclusões e desproteções sociais, características do atual modelo neoliberal criador de insegurança (2) . Inclui-se nesse contexto a Atenção à Saúde e a promoção do cuidado em áreas vulneráveis à violência, comumente caracterizadas por uma infraestrutura precária, em privação de condições materiais de vida e profundas desigualdades sociais.…”
Section: Introductionunclassified
“…Inclui-se nesse contexto a Atenção à Saúde e a promoção do cuidado em áreas vulneráveis à violência, comumente caracterizadas por uma infraestrutura precária, em privação de condições materiais de vida e profundas desigualdades sociais. Além das questões sociais, as pessoas que residem no território vivenciam situações de exclusão, a exemplo do desemprego, da falta de saneamento básico, da presença de lixo a céu aberto e da escassez de lazer e segurança (1,2) . O cuidado em saúde nessas áreas demanda a adequação do serviço à realidade local, o que pode representar inúmeros desafios para sua promoção efetiva.…”
Section: Introductionunclassified
See 1 more Smart Citation